Liquid‐ and Solid‐based Separations Employing Ionic Liquids for the Recovery of Platinum Group Metals Typically Encountered in Catalytic Converters: A Review. Issue 6 (9th February 2022) - Lanaridi, Olga; Schnürch, Michael; Limbeck, Andreas; Schröder, Katharina
Abstract: The wide application range and ascending demand for platinum group metals combined with the progressive depletion of their natural resources renders their efficient recycling a very important and pressing matter. Primarily environmental considerations associated with state‐of‐the‐art recovery processes have shifted the focus of the scientific community toward the investigation of alternative recycling approaches. Within this context, ionic liquids have gained considerable attention in the last two decades chiefly sparked by properties such as tunabilty, low‐volatility, and relatively easy recyclability. In this review an understanding of the state‐of‐the‐art processes, including their drawbacks and limitations, is provided. The core of the discussion is focused on platinum group metal recovery with ionic liquid‐based systems. A brief insight in some environmental considerations related to ionic liquids is also provided while some discussion on research gaps, common misconceptions related to ionic liquids and outlook on unresolved issues could not be absent from this review. Abstract : Ionic liquids to the rescue ? The scarcity of platinum group metals as well as the environmental impact associated with the state‐of‐the‐art processes for their recycling have shifted the focus of the scientific community toward alternative approaches. Herein, the research performed on platinum group metal recovery with the aid of ionic liquids is discussed in detail, while attention is drawn to their environmental impact. A critical look into the current research gaps and omissions is also provided.